Depression morphology of Bayan Lake, Zavkhan province, Western Mongolia: implications for the origin of lake depression in Mongolia. (2nd November 2022) - Enkhbold, Altanbold; Khukhuudei, Ulambadrakh; Kusky, Timothy; Tsermaa, Baatarchuluun; Doljin, Dash
ABSTRACT: Data on the origin and morphology of lake depressions in Mongolia are relatively poor. Bayan Lake in Zavkhan Province, Western Mongolia, has freshwater, supplied by groundwater emanating from a tectonic fault-oriented northeast to southwest, defining the southeastern side of the Bayan Lake. The depression of Bayan Lake has a tectonic origin, related with the fault which on its southern side, which is covered by sand dunes. The results of morphometric analysis, satellite mapping, geomagnetic anomaly assessment, and other relevant methods all support that the southern margin of the lake is defined by a large fault. The depression morphology of Bayan Lake shows that it was formed by subsidence accommodated by the fault along the southwestern side of the lake. Bayan Lake depression has the origin tectonic, but the recent barrier in the south is the dunefield on the bedrock.